Endoscopic Management of Complicated Highgrade Vesicoureteral Reflux in the First Year of Life - Ali Tekin; Sibel Tiryaki; İsmail Yağmur; Özge Kılıç; Ali Avanoğlu; İbrahim Ulman (Galenos Yayinevi, 2021)
Aim:The treatment of vesicoureteral reflux (VUR) in infants is controversial. Subureteric injection is considered by some to be a popular alternative to long-term antibiotic prophylaxis. In this study, we reviewed our experience in endoscopic subureteric injection to correct highgrade reflux in infants with documented indications for antireflux surgery.Materials and Methods:The hospital records of patients with grade 4-5 VUR and breakthrough urinary tract infections who had undergone endoscopic subureteric injection in the first year of life between 2009 and 2016 were reviewed retrospectively. Radiologic success was defined as complete resolution of reflux determined via voiding cystourethrogram obtained at least three months after the injection, and clinical success was defined as the downgrading of reflux grade to below three and the absence of urinary infection.Results:A total of 23 patients (5 girls, 18 boys) with 34 high-grade refluxing units were included in this study. The mean age at first injection was 6.3±1.8 months (1-11 months). The radiologic success rate with initial injection was 61.7%, and it was 85.2% after repeated injections. The overall clinical success rate after first injection was 70.6% and 97.1% after repeated injections. The mean injected material volume was 0.34±0.27 (0.1-1) mL per ureter.Conclusion:The management of high-grade infantile reflux is still controversial with insufficient data. Published studies comparing endoscopic treatment and antibiotic prophylaxis have inconclusive results due to their wide range of success rates. Although it needs to be supported by prospective studies, endoscopic treatment is a successful alternative in high-grade VUR infants with breakthrough infection.